0 . 0 5 1 0 0 0 r = 0 ∑ ∞ ( 1 0 0 0 + r ) ( 1 0 0 0 1 0 0 0 + r ) 0 . 9 5 r = ?
( n m ) = n ! ( m − n ) ! m ! denotes the binomial coefficient .
All of my problems are original .
This section requires Javascript.
You are seeing this because something didn't load right. We suggest you, (a) try
refreshing the page, (b) enabling javascript if it is disabled on your browser and,
finally, (c)
loading the
non-javascript version of this page
. We're sorry about the hassle.
We start with the geometric series, r = 0 ∑ ∞ p r = 1 − p 1 , where ∣ p ∣ < 1 . By diffferentiating this equation with respect to p for a total of n times, we will get r = 0 ∑ ∞ ( n r + n ) p r = ( 1 − p ) n + 1 1 . Hence, r = 0 ∑ ∞ ( r + n ) ( n r + n ) p r 0 0 0 0 = = = = = r = 0 ∑ ∞ ( r + n + 1 − 1 ) ( n r + n ) p r r = 0 ∑ ∞ ( r + n + 1 ) ( n r + n ) p r − r = 0 ∑ ∞ ( n r + n ) p r d p d [ r = 0 ∑ ∞ ( n r + n ) p r ] − [ r = 0 ∑ ∞ ( n r + n ) p r ] ( 1 − p ) n + 2 n + 1 − ( 1 − p ) n + 1 1 ( 1 − p ) n + 2 p + n In this case, n = 1 0 0 0 , p = 0 . 9 5 , r = 0 ∑ ∞ ( r + 1 0 0 0 ) ( 1 0 0 0 r + 1 0 0 0 ) ⋅ 0 . 9 5 r = 0 . 0 5 1 0 0 2 0 . 9 5 + 1 0 0 0 ⇔ 0 . 0 5 1 0 0 0 r = 0 ∑ ∞ ( r + 1 0 0 0 ) ( 1 0 0 0 r + 1 0 0 0 ) ⋅ 0 . 9 5 r = 0 . 0 5 2 1 0 0 0 . 9 5 = 4 0 0 3 8 0 .
Excellent solution sir. Thanku for sharing it with us. :)
Problem Loading...
Note Loading...
Set Loading...
Let n = 1 0 0 0 and p = 0 . 0 5
E = p n r = 0 ∑ ∞ ( n + r ) × ( n n + r ) × ( 1 − p ) r
E = n ! p n r = 0 ∑ ∞ ( n + r ) × ( r + 1 ) ( r + 2 ) … ( r + n ) × ( 1 − p ) r
Let's evaluate above sum.
Let,
S = r = 0 ∑ ∞ ( r + 1 ) ( r + 2 ) ( r + 3 ) … ( r + n ) × x r
x S = r = 0 ∑ ∞ ( r + 1 ) ( r + 2 ) ( r + 3 ) … ( r + n ) × x r + 1
S ( 1 − x ) = r = 0 ∑ ∞ n × ( r + 1 ) ( r + 2 ) ( r + 3 ) … ( r + n − 1 ) × x r
x S ( 1 − x ) = r = 0 ∑ ∞ n × ( r + 1 ) ( r + 2 ) ( r + 3 ) … ( r + n − 1 ) × x r + 1
S ( 1 − x ) 2 = r = 0 ∑ ∞ n ( n − 1 ) × ( r + 1 ) ( r + 2 ) ( r + 3 ) … ( r + n − 2 ) × x r
Continuing, we get
S ( 1 − x ) n = r = 0 ∑ ∞ n × ( n − 1 ) × ( n − 2 ) × … × 2 × 1 × x r = n ! r = 0 ∑ ∞ x r
S = ( 1 − x ) n + 1 n !
Let, k ∈ R − and
f ( k ) = r = 0 ∑ ∞ e k ( n + r ) × ( r + 1 ) ( r + 2 ) … ( r + n ) × x r
f ( k ) = e k n r = 0 ∑ ∞ ( r + 1 ) ( r + 2 ) … ( r + n ) × x r e k r
Comparing with S , we get
f ( k ) = r = 0 ∑ ∞ e k ( n + r ) × ( r + 1 ) ( r + 2 ) … ( r + n ) × x r = ( 1 − x e k ) n + 1 e k n n !
f ′ ( k ) = r = 0 ∑ ∞ e k ( n + r ) × ( n + r ) × ( r + 1 ) ( r + 2 ) … ( r + n ) × x r = ( 1 − x e k ) n + 2 n e k n ( 1 − x e k ) + e k n ( n + 1 ) × e k x n !
Now , x = 1 − p
f ′ ( 0 ) = r = 0 ∑ ∞ ( n + r ) × ( r + 1 ) ( r + 2 ) … ( r + n ) × x r = n ! p n + 2 ( n + 1 ) − p
E = n ! p n f ′ ( 0 )
E = p 2 ( n + 1 ) − p
Putting n = 1 0 0 0 and p = 0 . 0 5 , we get
E = 4 0 0 3 8 0